Minat Latihan Karate Atlet Inkanas Kabupaten Pangkep pada Masa Pandemi - Dahlan Dahlan; Muslim Muslim (Jurnal Penelitian Kesehatan SUARA FORIKES, 2023)
Since the spread of the COVID-19 pandemic, the activities of athletes have been greatly disrupted, so this has affected athletes' interest in pursuing karate training activities. The purpose of this study was to find out the extent of the interest in practicing karate athletes in Pangkep Regency during the pandemic. The approach in this study was quantitative, in the form of a descriptive study on karate athletes from SMAN 11 Pangkep. The study population was 65 karateka who practiced at SMAN 11 Pangkep branch and the sample size was 30 karateka who were selected by simple random sampling method. Interest data was collected by questionnaire method. Data analysis was performed using descriptive statistical methods including frequency and percentage. Based on the results of the study, it was known that interest is impaired: very good category = 0%, good = 30 (100%), enough = 0%, less = 0%. The conclusion of the study was that the interest in practicing Inkanas karate athletes during the pandemic at Pangkep 11 Senior High School was good.Keywords: karate athletes; interest in practicing; the COVID-19 pandemic ABSTRAK Sejak penyebaran pandemi COVID-19, kegiatan atlet menjadi sangat terganggu, sehingga hal ini mempengaruhi minat atlet dalam menekuni kegiatan latihan karate. Tujuan penelitian ini adalah adalah mengetahui sejauh mana minat berlatih atlet karate Inkanas Kabupaten Pangkep di masa pandemi. Pendekatan dalam penelitian ini adalah kuantitatif, berupa studi  deskriptif pada atlet karate Ranting SMAN 11 Pangkep. Populasi penelitian adalah 65 karateka yang berlatih di ranting SMAN 11 Pangkep dan ukuran sampel adalah 30 karateka yang dipilih dengan metode simple random sampling. Data tentang minat dikumpulkan dengan metode angket. Analisis data dilakukan dengan metode statistika deskriptif yaitu frekuensi dan persentase. Berdasarkan hasil penelitian diketahui bahwa distrubis minat adalah: kategori baik sekali = 0%, baik = 30 (100%), cukup = 0%, kurang = 0%. Kesimpulan penelitian ialah bahwa minat latihan atlet karate Inkanas pada masa pandemi pada Ranting SMAN 11 Pangkep adalah baik.Kata kunci: atlet karate; minat berlatih; pandemi COVID-19